Symptomatic Solitary Osteochondroma of the Subaxial Cervical Spine in a 52-Year-Old Patient - Vijay Sekharappa; Rohit Amritanand; Venkatesh Krishnan; Kenny Samuel David (Asian Spine Journal, 2014)
Osteochondromas are the most common benign tumors of the bone. They mostly arise from the appendicular skeleton and present clinically in the second or third decade of life. Ostechondromas arising from the subaxial cervical spine and presenting after the 5th decade of life are extremely rare. We report a 52-year-old male patient who presented with numbness and subjective weakness of left upper and lower limbs and neck pain, and had lobulated bony hard fixed swelling in the right lower cervical paraspinal region. Radiological images revealed a bony swelling arising from C4 and C5 lamina with a cartilaginous cap and intraspinal extension. Excision biopsy with stabilisation of the spine was performed. Histopathalogical examination of the specimen confirmed the diagnosis of osteochondroma. We conclude surgical excision of such rare tumors, including the cartilaginous cap as well as the intraspinal component can reliably produce a good clinical outcome.